Memetakan Publikasi Ilmiah tentang Penggunaan Media Sosial untuk Kampanye Politik: Analisis Bibliometric dengan Bibliometrix R-package - Firdauz, Dimas Lazuardy; Sobari, Nurdin (Universitas Negeri Surabaya, 2024)
The role of social media in political campaigns has been a significantly growing phenomenon over the past two decades. The proliferation of this new medium has prompted various evolving research questions aligning with the increasingly progressive practices of digitalizing political campaigning. Considering tracking advancements in this field, the study analyzes the publication trends and patterns in scholarly journals and conference proceedings about the utilization of social media in political campaigns from 2008 to 2023. Employing a qualitative science mapping approach, data are extracted from the Scopus database using keywords related to social media usage in political campaigns during the specified timeframe. Data analysis uses the recent science mapping R package called Bibliometrix, supplemented by network mapping visualization and keyword density analysis using VOSviewer. Findings reveal a notable increase in publications, with the United States emerging as the foremost contributor, demonstrating a more than eighty percent increase since 2011. Our study found that Information Communication and Society is the top publisher, and the University of California has the most institutional affiliations. Twitter is the most researched social media platform, and recent publications focus on using computation-based techniques like machine learning and natural language processing to study social media in political campaigns